The Role of Microfinance Institutions in Micro, Small and Medium Enterprises (MSMES): a Case Study of Budi Gadai - Roren, Yeli; Puan, Adinda; Bonamanobing, Rizky; Alviansha, Alwi (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study examines the role of microfinance institutions in supporting the development of Micro, Small, and Medium Enterprises (MSMEs), with a case study on Budi Gadai, located on Jalan Pancing. The objective of this research is to analyze how microfinance, particularly Budi Gadai, contributes to the growth and sustainability of MSMEs through accessible financing and financial management guidance. The research employs a qualitative approach with in-depth interviews and analysis of business performance data from MSME clients of Budi Gadai. The findings indicate that Budi Gadai provides a significant impact on MSME growth by offering simplified loan access, which helps business owners overcome financing barriers. The majority of MSMEs reported increased revenue and business expansion after obtaining funding from Budi Gadai. However, challenges remain, such as high interest rates and limited loan amounts. Nevertheless, Budi Gadai plays a critical role in the economic resilience of MSMEs, especially during periods of financial crisis. This study concludes that microfinance institutions like Budi Gadai are essential for the sustainability and growth of MSMEs, particularly in urban areas.